(untitled) (Environmental Smoke, 2025)
This study aims to present an integrative literature review on the use of herbal medicines in the treatment of skin diseases in dogs. The research was carried out through literature search or sampling, using the electronic databases National Center for Biotechnology Information (PubMed), Scientific Electronic Library Online (SciELO) and Portal de Periodicals da Capes (Capes), between April and October 2023. The following descriptors and their combinations in Portuguese, Spanish and English were used: "dermatological diseases", "dogs", "treatment", "herbal medicines", "essential oils" and "plant extract". Ten articles that met the inclusion criteria and answered the guiding question were selected. The results indicate that herbal medicines have shown potential in the treatment of skin diseases in dogs, since many plants have antimicrobial, anti-inflammatory and healing activity, which can contribute to the improvement of symptoms and skin regeneration. However, more studies are needed to evaluate their specific efficacy in different canine dermatological conditions. The use of these products should always be guided by a veterinarian, taking into account the individual characteristics of the animal, considering factors such as the severity of the skin disease, the animal’s medical history, interactions with other medications in use and seeking to ensure the safety and well-being of the pet.